Upaya Meningkatkan Hasil Belajar IPA Melalui Penggunaan Media Animasi di SDN-1 Bukit Tunggal - Yandi Prayuda; Miftahurrizqi Miftahurrizqi (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to determine the improvement of science learning outcomes and describe the activities of students after using learning with animation media in fourth-grade students of SDN-1 Bukit Tunggal. This study uses classroom action research methods that are used to obtain results from efforts to improve learning outcomes of science through the use of animation media at SDN-1 Bukit Tunggal. Data collection techniques use observation, documentation, and test techniques. While for data analysis using the formula for class average values, classical percentage completeness, and N-Gain. The results of this study indicate that: there is an increase in science learning outcomes through the use of animation media in grade IV students of SDN-1 Bukit Tunggal with subject matter recognizing human skeletons with an average grade value of 84.83 and classical completeness of 96.66 %, and increased learning outcomes by 0.67.